A aplicabilidade da agenda de trabalho decente para proteção do trabalhador migrante no Brasil - Côrtes, Priscila Cavalcanti (2019)
The present study seeks to analyze the current perspectives for the implementation of decent workingconditions for migrants in Brazil, who come to the country in a marginalized way, requiring the reception of public institutions in order to respect their Fundamental Rights. The analysis will take as its starting point the Decent Work Agenda promoted by the International Labor Organization and its impacts on Brazil.